2021
DOI: 10.1177/20458940211021528
|View full text |Cite
|
Sign up to set email alerts
|

SU5416 plus hypoxia but not selective VEGFR2 inhibition with cabozantinib plus hypoxia induces pulmonary hypertension in rats: potential role of BMPR2 signaling

Abstract: Introduction: SU5416 plus chronic hypoxia causes pulmonary arterial hypertension (PAH) in rats and is assumed to occur through VEGFR2 inhibition. Cabozantinib is a far more potent VEGFR2 inhibitor than SU5416. Therefore, we hypothesized that cabozantinib plus hypoxia would induce severe PAH in rats. Methods: Cell proliferation and pharmacokinetic studies were performed. Rats were given SU5416 or cabozantinib SC or via osmotic pump and kept hypoxic for 3 weeks. Right ventricular systolic pressure (RVSP) and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…This newly identified angiogenic response appears to be essential for the adaptation to acute hypoxic exposure and maintenance of EC function but was suppressed after treatment with SU5416, a VEGFR2 TKI. It has been shown that cabozantinib, which is a more potent VEGFR2 TKI, could not induce severe PH in hypoxic rats and SU5416 might exert a pathogenic effect via combined VEGFR2 and BMPR2 signaling inhibition ( 10 ) and/or activation of aryl hydrocarbon receptor signaling ( 24 ) under hypoxic conditions. However, in the present study, administration of cabozantinib to hypoxic mice exacerbated Hx-PH with suppression of Ppargc1a and Vegfa expression as well as SU5416.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This newly identified angiogenic response appears to be essential for the adaptation to acute hypoxic exposure and maintenance of EC function but was suppressed after treatment with SU5416, a VEGFR2 TKI. It has been shown that cabozantinib, which is a more potent VEGFR2 TKI, could not induce severe PH in hypoxic rats and SU5416 might exert a pathogenic effect via combined VEGFR2 and BMPR2 signaling inhibition ( 10 ) and/or activation of aryl hydrocarbon receptor signaling ( 24 ) under hypoxic conditions. However, in the present study, administration of cabozantinib to hypoxic mice exacerbated Hx-PH with suppression of Ppargc1a and Vegfa expression as well as SU5416.…”
Section: Discussionmentioning
confidence: 99%
“…Cabozantinib was purchased from LC Laboratories and suspended using sonication in a mixture of 0.5% carboxymethylcellulose sodium, 0.9% sodium chloride, 0.4% polysorbate 80, and 0.9% benzyl alcohol in deionized water. CabHx mice were injected once weekly with cabozantinib at 20 mg/kg BW during hypoxic exposure ( 10 ). Baicalin (CAS 21967-41-9) was purchased from Merck KGaA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SU5416 can specifically bind to ECs, enriched in the membrane and thence slowly released into the cytoplasm, which ensures long‐term inhibition of VEGFR 24 . Loss of EC growth signal, inflammation and oxidative stress due to inhibition of VEGFR, TGF‐β/BMP/Smad, Hif‐1α, mitogen‐activated protein kinase (MAPK), aryl hydrocarbon receptor (AhR) and other signaling pathways are involved in the regulation of the SU5416/hypoxic (SuHx) PH model 21,25,26 . Sharing other hallmarks (concentric laminar and plexiform lesions) of human PAH, the rodent SuHx PH model is regarded as a more appropriate preclinical model of occlusive PAH than the CHPH models, particularly for genetic modification or long‐term intervention 27‐29 …”
Section: Non‐invasive Models In Vivomentioning
confidence: 99%
“…In addition, Sitapara et al. reported that Sugen 5416 affects BMPRII signaling, 16 providing yet another possible explanation for the development of PAH like vascular lesions after the double challenge of Sugen and hypoxia.…”
mentioning
confidence: 99%